English Ability Assessment for Economic Analysis of Employment and Income in Cambodian Frontline Staff - Morrow, Jeffrey Stewart (Journal of Tourism Management Research, 2016)
Tourism in Cambodia has grown remarkably since the early 2000’s; the influx of international travelers meant that tourist industry (TI) frontline employees have needed top-level English communication ability. Since background data in Cambodia has been lacking, the author wanted to verify the role of English communication ability (ECA) in TI employees in Siem Reap city to fill this gap. During four surveys over five years, the author collected background as well as ECA data. To more accurately measure ECA numerically as a means for other researchers to conduct further studies, the author designed an assessment test loosely based on the CEFR. In statistical analysis of income with English variables, high positive correlations were found in English communication ability, years and hours of English education, and monthly expenditure for English learning. Therefore, it can be said that there is a significant relationship between ECA, better employment, and higher incomes in TI employees there. This scale could be profitably used via the Internet to conduct similar research in similar situations.